Electromyographical kinesiology : Proceedings of the 8th Congress, held in Baltimore, 12-16 August 1990 - Anderson, Paul; Hobart, Donald J; Danoff, Jerome V (Excerpta Medica, 1991)
The scientists who gathered at the Congress of ISEK to share advances and knowledge in the broad field of Electrophysiological Kinesiology are bound together by a common desire to study human movement and the neuromuscular system. This book is a selection of the one hundred and thirty one platform papers and eleven \"state-of-the-art\" sessions from 11 invited speakers, representing a distinguished scientific group. The book is offered as a contribution to the body of knowledge for the neuromuscular system in normal and diseased states. It includes both basic and applied research.
Excerpta medica. 949, International congress series
Keywords: kinesiologie elektromyografická - aplikace - sborníky prací; elektrofyziologové - konference/Baltimore,1990/ - sborníky prací; fyziologie; rehabilitační a fyzikální medicína